Practical improvements in causally-interpretable meta-analysis and transportability - Rott, Kollin (My University, 2024)
No abstract included.
University of Minnesota Ph.D. dissertation. August 2024. Major: Biostatistics. Advisors: James Hodges, Jared Huling. 1 computer file (PDF); v, 82 pages.
Keywords: causal inference; meta-analysis; transportability